NON-MUTAGENIC AND IN VITRO TOXICITY EVALUATION OF EMBELIN ON HUMAN PERIPHERAL BLOOD LYMPHOCYTES AND MOUSE MACROPHAGES - SUMALATHA K.R,; SREEPRIYA M, (International Journal of Pharma and Bio Sciences, 2015)
The development of novel drugs that have chemotherapeutic activity against cancer is a great challenge. The discoveries of these drugs are very difficult, because they must be able to destroy the tumor cells without causing adverse side effects. Significant innovations come forth when human cell lines are used for vetting drugs and other chemicals. Embelin, a benzoquinone is reported to possess anticancer activity on various cancer cell lines. The present investigation was undertaken to determine the toxicity profile of embelin on human peripheral blood lymphocytes and murine macrophages. The effect of embelin on growth and viability of cells was determined by MTT assay. Further embelin was tested for mutagenicity by the Ames test, in Salmonella typhimurium strains with and without metabolic activation. Results implicate that embelin was non mutagenic in the tester strains used in the study and did not adversely influence the proliferation of lymphocytes and macrophages and the IC50 was found to be 78.7µg/ml and 128.54µg/ml respectively.